Să se rezolve ecuația:
(3x-2)²+4(2+3x)²≤20(x-3)²
Răspunsuri la întrebare
Răspuns de
1
(3x-2)²+4(2+3x)²≤20(x-3)²
9x²-12x+4+16+48x+36x²≤20x²-120x+180
45x²+36x+20≤20x²-120x+180
45x²+36x+20-20x²+120x-180≤0
25x²+156x-160≤0
9x²-12x+4+16+48x+36x²≤20x²-120x+180
45x²+36x+20≤20x²-120x+180
45x²+36x+20-20x²+120x-180≤0
25x²+156x-160≤0
Alte întrebări interesante
Informatică,
8 ani în urmă
Biologie,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
9x²-12x+4+4(4+12x+9x²)≤20(x²-6x+9)
9x²-12x+4+16+48x+36x²≤20x²-120x+180
45x²+36x+20≤20x²-120x+180
45x²+36x+20-20x²+120x-180≤0
25x²+156x-160=0
Δ=156²-4*25*(-160)=40336